STUDY THE EFFECT OF ADDITION NANO ZINC OXIDE ON THE VEGETATIVE, FLOWERING AND FRUITING CHARACTERISTICS OF GROWING Capsicum frutescens PLANT IN CLOSED HYDROPONICS SYSTEM - AL-Zuhairi, Osama G.; AL-Mahdawi, Muthana M.; Hammadi, Mustafa A. (Diyala Agricultural Sciences Journal, 2020)
The study included tow experiments, the first laboratory and the second field experiment, for the period from 1/2/2018 to 1/11/2018, The laboratory experiment was performed in the laboratories of the College of Education for Pure Sciences / University of Diyala, where nano- ZnO have been prepared by Co-Precipitation and. The field experiment was conducted inside the plastic house follow of the Baquba nursery / Department of Agricultural of Diyala. To study effect of adding concentrations 0, 25 and 75 mg.l-1 of Nano zinc oxide to the nutrient solution of Capsicum frutescens L. plant using technical of closed hydroponics system. The results of the laboratory experiment showed to that zinc oxide prepared is a nanoparticles, depending on the data obtained from the measurement of diffraction X-Ray, , As confirmed the energy dispersive X- ray spectroscopy (EDX) that the material is free of impurities. Also, showed scanning electron microscopy (SEM) that zinc oxide prepared is a nanoparticles. The results of the field experiment showed to that use of ZnO at 75 mg/l concentration caused significantly influenced in Plant Height and at a rate of 61.0 cm, stem diameter at a mean of 10.3mm , leaf area at a mean of 32.0 cm2 ,branch number at a mean of 29.4 branch/plant and leaves number at a mean of 248.0 leaf/ plant, compared with the control treatment which gave a rate of 55.0 cm for Plant Height, stem diameter at a mean of 9.1mm , leaf area at a mean of 25.0 cm2 ,branchs number at a mean of 23.5 branch/plant and leaves number at a mean of 234.3 leaf/ plant and, the same concentration caused significantly influenced in the flowers number and fruits number and yield of plant at a rate of 75 flower/plant , 16.8 fruit/ plant and 119.2 gm/plant respectively. While the control treatment gave a rate of 43 flower/plant , 9.0 fruit/ plant and 64.0 gm/plant respectively.